WHY IS CONFUCIANISM NOT A RELIGION? THE IMPACT OF ORIENTALISM: Editorial & Introductionwith Willem B. Drees, "Zygon Goes Global: East Asian Voices"; and Thomas John Hastings, "Extending the Global Academic Table: An Introduction." Where Are We?with CHEN Na, "Why Is Confucianism Not a Religion? The Impact of Orientalism"; KAMATA Toji, "Shinto Research and the Humanities in Japan"; KIM Seung Chul, "Religion and Science in Dialogue: An Asian Christian View"; and LEE Yu‐Ting, "East Asia and Human Knowledge – A Personal Quest." How Did We Get There?with HSU Kuang‐Tai, "Science and Confucianism in Retrospect and Prospect"; SI Jia Jane and DONG Shaoxin, "Humanistic Approach of the Early Protestant Medical Missionaries in Nineteenth‐Century China"; and ZHAO Aidong, "American Missionaries Transmitting Science in Early Twentieth‐Century Eastern Tibet." East Asian Engagements with Sciencewith Thomas John Hastings, "Kagawa Toyohiko (1888–1960): Witness to the Cosmic Drama"; INAGAKI Hisakazu, "Kagawa's Cosmic Purpose and Modernization in Japan"; HYUN Woosik, "An East Asian Mathematical Conceptualization of the Transhuman"; KANG Shin Ik, "Jumping Together: A Way from Sociobiology to Bio‐Socio‐Humanities"; FUKUSHIMA Shintaro, "Multilayered Sociocultural Phenomena: Associations between Subjective Well‐Being and Economic Status"; and SHIN Jaeshik, "Mapping One World: Religion and Science from an East Asian Perspective.". Issue 1 (March 2016) - Na, Chen
Abstract: This study attempts to answer the question why Confucianism, the dominant "teaching" among the Three Teachings, is not a religion in contemporary China, unlike the other two "teachings, " Buddhism and Daoism. By examining this phenomenon in the social‐historical context, this study finds its origin in Orientalism. The Orientalist conceptualization of religion became part of the New Culture discourse at the turn of the twentieth century. While China has undergone tremendous social changes over the past century, the old discourse remains.